Blood biomarker changes and relationships after low dose oral ketamine treatment for post-traumatic stress disorder (PTSD) - Bonnie L. Quigley; Emerald Orr; Sophie Kafka; Maryam Hajishafiee; Ana P. Bouças; Nathan Wellington; Megan Dutton; Monique Jones; Fiona Randall; Jim Lagopoulos; Adem T. Can; Daniel F. Hermens (Psychopharmacology, 2026)
Rational Ketamine has been investigated as a treatment alternative for PTSD for the last 20 years, yet there have been limited reports of biological changes or biomarker characterisation related to treatment. Objectives To address this significant gap, this study analysed blood samples from 25 participants with PTSD who took part in an open-label 6-week trial of low dose oral ketamine treatment. Methods Serum and plasma samples were quantified before and after ketamine treatment for brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor A (VEGF-A), serotonin, FK506 binding protein 51 (FKBP51) and a panel of cytokines (interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-12p70, IL-17 A and tumour necrosis factor alpha (TNFα)). Results Analysis of BDNF and VEGF-A levels from serum detected a significant positive correlation between the two biomarkers and a small but statistically significant decrease in both measures after ketamine treatment. This novel finding reinforces theories that ketamine’s effects may rely on a reciprocal interaction between BDNF and VEGF-A, offering potential insights into a biological mechanism underpinning PTSD symptom reduction. Additionally, the analysis of FKBP51 and serotonin revealed novel relationships between these biomarkers and clinical scales, before and after ketamine treatment. Finally, significant changes or relationships involving the immune cytokines were not detected, possibly because half the participants presented with low-grade inflammation while the other half did not. Conclusions This study represents a much-needed broad analysis of blood biomarkers before and after ketamine treatment for PTSD and reveals important biological changes and relationships related to this treatment.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Oral ketamine may offer a solution to the ketamine conundrum - Megan Dutton; Adem T. Can; Jim Lagopoulos; Daniel F. Hermens (Psychopharmacology, 2023)
Ketamine has received considerable attention for its rapid and robust antidepressant response over the past decade. Current evidence, in clinical populations, predominantly relates to parenterally administered ketamine, which is reported to produce significant undesirable side effects, with additional concerns regarding long-term safety and abuse potential. Attempts to produce a similar drug to ketamine, without the psychotomimetic side effects, have proved elusive. Orally administered ketamine has a different pharmacological profile to parentally administered ketamine, suggesting it may be a viable alternative. Emerging evidence regarding the efficacy and tolerability of oral ketamine suggests that it may be a favourable route of administration, as it appears to obtain similarly beneficial treatment effects, but without the cost and medical resources required in parenteral dosing. The pharmacological effects may be due to the active metabolite norketamine, which has been found to be at substantially higher levels via oral dosing, most likely due to first-pass clearance. Despite bioavailability and peak plasma concentrations both being lower than when administered parenterally, evidence suggests that low-dose oral ketamine is clinically effective in treating pain. This may also be due to the actions of norketamine and therefore, its relevance to the mental health context is explored in this narrative review.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Why ant pollination is rare: new evidence and implications of the antibiotic hypothesis - Emily M. Dutton; Megan E. Frederickson (Arthropod-Plant Interactions, 2012)